Further Austerity and Wage Cuts Will Worsen the Euro Crisis - Corrado Andini; Ricardo Cabral (Institute for the Study of Labor (IZA), 2012)
This note argues that the solutions to the euro-area crisis proposed by the EU governing institutions in cooperation with the IMF, based on further austerity and wage cuts, will worsen the crisis. They are unlikely to reduce both sovereign and external debt ratios of countries experiencing these problems. Quite in contrary, they are likely to further reduce the real GDP growth of these countries.
Keywords: E1; E4; E5; E6; 330; euro crisis; austerity; wage cuts; Haushaltskonsolidierung; Lohnpolitik; Wirkungsanalyse; Staatsbankrott; Wirtschaftskrise; Eurozone